Menejemen Keselamatan Pasien Sebagai Upaya Peningkatan Mutu Pelayanan Kesehatan - Nur Andani; Rezqiqah Aulia Rahmat; Dwi Ardyna Octa Sari (Barongko: Jurnal Ilmu Kesehatan, 2026)
Patient safety is a key component of healthcare quality. Patient safety incidents can undermine service quality and public trust in healthcare facilities. Patient safety management is needed as a systematic approach to prevent service errors and minimize the risk of patient harm. This study aims to examine the role of patient safety management in efforts to improve healthcare quality. The study used a descriptive design with a qualitative approach through a literature review and observation of patient safety implementation. The results indicate that the implementation of good patient safety management contributes to improved service quality, patient satisfaction, and safety culture in healthcare facilities. The study concludes that patient safety management is an important strategy for continuously improving healthcare quality.